The effect of concentration of cinnamon extract and storage time on physicochemical, microbial and sensory attributes of avocado juice - Zemenu Tadesse Adimas; Takele Ayanaw Habitu; Mekuannt Alefe Adimas; Biresaw Demelash Abera (Applied Food Research)
Avocado juice usage is a global challenge due to microbial and lipid oxidation, leading to the use of synthetic preservatives to prolong shelf life and maintain quality. Concerns about the negative health impacts of chemical additives are leading consumers to shift towards natural preservatives like cinnamon powder in avocado juice production. The study investigates the impact of cinnamon extract concentration ratio and storage time on avocado juice's quality, shelf life, physiochemical, antimicrobial, and sensory properties. Avocado juice was produced at different ratios of cinnamon extract (C0 = 0, C1 = 1, C2 = 2, and C3 = 3%) and stored for 0, 4, 8, and 12 h. The study found that increasing cinnamon extract concentration enhances sensory properties of avocado juice and decreases physiochemical properties except pH value. However, as the storage time increased, the physicochemical, microbial and sensory properties of avocado decreased. The study found high microbial load and less preferred sensory attributes of avocado juice with low cinnamon extract percentage and long storage time. Cinnamon extract, with its antimicrobial and antioxidant properties, has potential as a natural preservative for avocado juice, potentially extending shelf life and preserving juice quality. Governments, food policy makers, and cafeteria owners should use cinnamon extract to prolong avocado juice shelf life.